A cinematic analysis of the leadership behaviours of Robin Hood. Issue 2 (15th March 2021) - Bartlett, Kenneth R.; Jang, Soebin; Feng, Ying; Aderibigbe, Eniola
ABSTRACT: This study conducts a critical examination of leadership behaviour practices in a selection of film adaptations of the Robin Hood legend. This paper extends traditional efforts with theorizing leadership beyond leaders and their followers to consider acted performance exhibitions of leadership through cultural artefacts. The theory of dramatism was used to consider the portrayal of leadership behaviours of the title character in six Robin Hood films released over the years 1922–2018. A coding scheme using the GLOBE study six global leadership dimensions and associated 21 primary leadership behaviours were used to examine the action and dialogue of acted behaviours in each scene in each film. The results showed that the Robin Hood character most frequently presented a charismatic/value-based leadership style across all films. The results are discussed in terms of the ability of film to explore issues of leadership with results highlighting how leadership traits and behaviours of traditional cultural legends evolve and are adapted to modern audiences. This study contributes to ongoing investigations of analysis of leadership from an HRD theory and practice lens as represented in cultural artefacts such as film.